The misfits [videorecording (DVD)] - Huston, John, 1906-1987; Gable, Clark, 1901-1960; Monroe, Marilyn, 1926-1962; Clift, Montgomery (MGM Home Entertainment, 2001)
Following her divorce, a lonely young woman befriends a couple of down-on-their-luck cowboys. Both men desire her, but she longs for only one, who represents for her the freedom she's never had. Teaming up with a weather-beaten rodeo rider, the foursome goes into the mountains on a quest for rare and elusive wild horses. There they come to realize that, for all their differences, they share fundamentally similar needs and desires.